ABILITY OF FINANCIAL TECHNOLOGY IN MEDIATING FINANCIAL LITERACY TOWARDS FINANCIAL INCLUSION - Solihatun Nisak; Hwihanus Hwihanus (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this study is to determine the effect of financial literacy through 3 concepts, namely financial awareness, financial experience and financial skills on financial inclusion which has not been widely studied before. This study also aims to determine the ability of financial technology in mediating the effect of financial literacy on financial inclusion. This study is a quantitative study to test the hypothesis. The population selected in this study were household. The sample was selected using the random sampling method with the number of samples using the lemeshow method, samples in this test is 100 person. Data were analyzed using path analysis with the SmartPLS4 analysis tool. From the results of data testing, it was obtained that financial awareness, experience and financial technology had a significant effect on financial inclusion, while financial skills had no significant effect. Financial experience and financial skills had a significant effect on financial technology, while financial awareness did not have a significant effect on financial technology. Indirect testing showed that financial technology was able to mediate the effect of financial experience and financial skills on financial inclusion. However, financial technology was unable to mediate the effect of financial awareness on financial inclusion.